EPCO-21. THE SPATIAL ORGANIZATION OF H3-K27M MUTANT DIFFUSE MIDLINE GLIOMA. (14th November 2022) - Liu, Ilon; Li, Jiang; Samuelsson, Erik; Salas, Sergio Marco; Beck, Alexander; Hack, Olivia; Jeong, Daeun; Shaw, McKenzie; Englinger, Bernhard; Labelle, Jenna; Mire, Hafsa; Madlener, Sibylle; et al.
Abstract: Histone 3 lysine27-to-methionine mutant diffuse midline gliomas (H3-K27M DMGs) are among the most lethal brain tumors. Their putative cellular hierarchy has been shown to be driven by self-renewing stem-like cells arrested in an oligodendrocyte precursor-like (OPC-like) state, of which few cells are able to differentiate towards more mature astrocyte (AC)-like and oligodendrocyte (OC)-like cells. However, the spatial organization underlying this tumor cell architecture and its microenvironmental interactions in intact H3-K27M DMG tissues remain unknown. Here, we profiled the single cell transcriptomes of 45 patient H3-K27M DMGs and derived cell population-specific marker gene combinations to characterize the single cell spatial organization of 16 tumors using targeted in situ sequencing. We thereby resolved different malignant and non-malignant cell populations including cycling, OPC-like, AC-like, OC-like, mesenchymal tumor cells, and non-malignant oligodendrocytes, astrocytes, neurons, myeloid cells, T cells, and vascular cells directly in situ . Global neighborhood analyses indicate a higher tendency of cycling OPC-like cells, vascular cells, and neurons to localize within a more restricted homogeneous compartment, whereas AC-like cells, non-malignant astrocytes and myeloid cells tend to intermingle with different cell populations in a more diffuse manner. Among malignant cells, we observed cycling OPC-like and OC-like cells to co-localize within a niche-like structure that is surrounded by more differentiated AC-like cells. We further validated this stem-like niche at the protein level using multiplexed immunofluorescence via the CODEX system. Finally, we characterized relationships between malignant and non-malignant cells, consistently identifying preferred neighborhoods of mesenchymal tumor cells with vascular and myeloid cells. Together, this study resolves the spatial architecture of H3-K27M DMG malignant and non-malignant cells at single cell resolution and identifies a local niche of the oligodendroglial lineage containing the OPC-like cancer stem-like cells, thus providing novel insights into the cancer stem-like compartment in H3-K27M DMGs and suggesting potential avenues for its perturbation.